Member of Editorial Board - Souleles, Nicos (My University, 2026)
The Journal includes several divisions of which Architecture and Arts is one. It encompasses scientific research in the various fields of design for interior or external architecture – all fields of applied fine arts and art education. Such research is conditioned to have clear vision and goal, adopting suitable research styles and methods, their results must add something new. The research must guarantee originality, creativity, the documentation and stability of references and resources. The modernization of the resources and their vitality among the international references. (https://mjaf.journals.ekb.eg/?lang=en)